Microbial dysbiosis in oral squamous cell carcinoma: A systematic review and meta-analysis. Issue 2 (February 2023) - Yu, Xiaoyun; Shi, Yongmei; Yuan, Rongtao; Chen, Zhenggang; Dong, Quanjiang; Han, Linzi; Wang, Lili; Zhou, Jianhua
Abstract: Objective: The aim of this study was to summarize previously published data and assess the alterations in the composition of the oral microbiome in OSCC using a systematic review and meta-analysis. Design: Electronic databases were systematically searched for studies on the oral microbiome in OSCC published before December 2021. Qualitative assessments of compositional variations at the phylum level were performed. The meta-analysis on abundance changes of bacteria genera was performed via a random-effects model. Results: A total of 18 studies involving 1056 participants were included. They consisted of two categories of studies: 1) case-control studies (n = 9); 2) nine studies that compared the oral microbiome between cancerous tissues and paired paracancerous tissues. At the phylum level, enrichment of Fusobacteria but depletion in Actinobacteria and Firmicutes in the oral microbiome was demonstrated in both categories of studies. At the genus level, Fusobacterium showed an increased abundance in OSCC patients (SMD = 0.65, 95% CI: 0.43–0.87, Z = 5.809, P  = 0.000) and in cancerous tissues (SMD = 0.54, 95% CI: 0.36–0.72, Z = 5.785, P  = 0.000). The abundance of Streptococcus was decreased in OSCC (SMD = −0.46, 95% CI: −0.88−0.04, Z = −2.146, P  = 0.032) and in cancerous tissues (SMD = −0.45, 95% CI: −0.78–0.13, Z = −2.726, P  = 0.006). Conclusions: Disturbances in the interactions between enriched Fusobacterium and depleted Streptococcus may participate in or prompt the occurrence and development of OSCC and could be potential biomarkers for detection of OSCC.